On the problem of retracting balls onto their boundary - Kazimierz Goebel (Abstract and Applied Analysis)
We provide some new estimates of the smallest possible Lipschitz constant for retractions of the unit ball B onto the unit sphere S in infinite-dimensional Banach spaces.